Fermented dairy products based on ovine cheese whey - Pereira, C. D. (2015)
This work presents an alternative solution for ovine whey components recovery in medium/small cheese plants that predominate in the rural areas of Southern European countries, which are specialized in the production of protected designation of origin (PDO) cheeses. These plants lack the capacity to concentrate and dry whey, and although a significant amount of this by-product is used in the manufacture of whey cheeses, in several cases it is used as animal feed or simply discarded. As an alternative to these practices, we propose the production of liquid whey protein concentrates (LWPC) by means of ultrafiltration (UF) followed by thermal denaturation and homogenization and their utilization in the production of fermented products based on kefir grains and/or commercial probiotic bacteria. Two types of fermented products were prepared: one in a liquid form (low protein and fat contents) and other in a gel form (high protein and fat contents). The microbiological, physicochemical (gross composition, pH, titratable acidity) and rheological properties of such products were assessed and compared during fermentation and at the 7th, 14th and 21st days of refrigerated storage. The fermented products presented adequate amounts of lactococci, lactobacilli (>7 Log10 CFUmL-1) and yeasts (>6 Log10 CFUmL-1). The rheological properties of liquid products were stable during the 21 days of refrigerated storage. However, gel type products showed variations in viscosity after 14 days, in the cases in which kefir grains were present. Although further work is needed in order to optimize the formulations regarding to the improvement of their sensory properties, it was concluded that this approach allows for the production of innovative fermented dairy products.